PENGGUNAAN MODEL PROBLEM BASED LEARNING ( PBL ) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SDN 04 BARIANG RAO – RAO KABUPATEN SOLOK SELATAN - Fauzana, Ulfa; Muhammadi, Muhammadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to describe the use of the Problem Based Learning (PBL) Model to Improve Student Learning Outcomes in Pancasila Education Learning in Class V SDN 04 Bariang Rao - Rao, South Solok Regency.  This type of research is Classroom Action Research (PTK).  The research results showed an increase in the teaching modules for cycle I 83.33% (Good) and cycle II 95.83% (Very Good).  The first cycle teacher activity assessment was 82.14% (Good) and the second cycle teacher activity assessment was 92.85% (Very Good).  Assessment of students in improving learning outcomes in cycle I was 82.14% and cycle II was 92.85%.  Based on these results, it can be concluded that the Problem Based Learning (PBL) model can improve student learning outcomes in learning Pancasila Education in class V.